Unlocking sustainable urban mobility: understanding the impact of motivational factors on dockless bike-sharing adoption within the knowledge-based economy - Zhao, Chenchen; Wang, Liangyu; Li, Mengyu; Chen, Xiangyu; Liu, Niwen (Springer Science and Business Media LLC, 2024)
In the wake of rapid urbanization, cities worldwide face critical challenges such as traffic congestion, air pollution, and excessive energy consumption. Governments have responded with initiatives aimed at sustainable development and greenhouse gas emission control. Sustainable urban transport measures, particularly dockless bike-sharing (DBS) systems, have emerged as key solutions. This paper investigates the psychological motivations behind users’ continuous adoption of DBS in China, employing the uses and gratification theory (UGT) as a theoretical framework. The study identifies three primary motivational dimensions: convenience gratification, achievement gratification, and environmental protection gratification. Convenience emerges as a foundational factor, driven by the flexibility and accessibility of DBS. Users who value utilitarian and hedonic aspects tend to be more motivated by convenience. Achievement gratification arises from users’ sense of accomplishment and physical activity, while environmental protection gratification is linked to reducing carbon emissions and alleviating traffic congestion. Perceived utilitarian and hedonic values moderate the relationships between these gratifications and continuous use. Also, demographic factors, including educational level, gender, and income, influence user behavior. Highly educated individuals and those with higher incomes show a greater propensity for continuous DBS use, while males exhibit a stronger inclination than females. Understanding these motivational factors and perceived values is crucial for policymakers, stakeholders, and service providers. Strategies that enhance convenience, achievement, and environmental consciousness can foster DBS adoption and contribute to sustainable urban mobility, aligning with the principles of the knowledge-based economy. However, the study acknowledges limitations related to its focus on the Chinese context, the use of convenience sampling, and the cross-sectional design. Future research should explore broader contexts, employ diverse sampling techniques, investigate additional influential factors, and use advanced statistical methods to further elucidate user behavior in urban mobility.